Pengaruh Product, Price, Place, Promotion (4P) Terhadap Peningkatan Penjualan Minuman Kedai Kopi Mikano - Oktori, Zidan Yuslian; Mega, Selfia Alke (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to evaluate the influence of product, price, place and promotion (4Ps) as elements of the marketing mix and the factors that have the most influence on increasing sales at Mikano Coffee Shop. Primary data was collected through interviews and questionnaires. The population of this study includes all consumers of Mikano coffee shop. For sampling, a non-probability method was used by distributing questionnaires to 50 respondents. Data analysis was performed using SPSS 26 software, with descriptive analysis and multiple linear regression. The research results show that Product, Price, Place, and Promotion (4P) have a positive impact on increasing sales, both partially and simultaneously. The promotion variable has the largest positive and significant impact on increasing sales at the Mikano Coffee Shop.